Avoiding oxygen-induced early fracture in titanium with high strength via entangled grains through laser powder bed fusion. (1st January 2023) - Chen, Kewei; Li, Hua; Huang, De Jun; Shen, Xiaojun; Jia, Ning
Abstract: Titanium (Ti) samples with oxygen contents of 0.13% (weight %) (0.13%O-Ti), 0.18% (0.18%O-Ti) and 0.24% (0.24%O-Ti) are printed through laser powder bed fusion (L-PBF) process. With increasing oxygen content, yield strength of L-PBF Ti under tensile testing increases without losing ductility, and becomes larger than that of conventionally produced Ti. Probably this is not resulted from even oxygen distribution, because nano-scale oxygen segregation is observed in 0.24%O-Ti through high-resolution scanning transmission electron microscopy (STEM). In order to get insight into fundamental mechanism of the oxygen-induced early fracture avoidance and high strength, tensile testing of L-PBF Ti is followed by quasi-in-situ electron backscatter diffraction (EBSD)/backscattered electron microscopy (BSEM). It is found that avoidance of the oxygen-induced early fracture and high strength are probably attributed to extensive entangled grains, which promotes formation of multiple slip systems and prevents the propagation of intergranular crack. Graphical abstract: Image, graphical abstract